Factors post abortion care utilization and associated factors among women of reproductive age in Lira City. A cross-sectional study. - Anena, Eunice; Auma , Anna Grace (Student's Journal of Health Research Africa, 2025)
Background PAC is an effective intervention for decreasing maternal mortality and morbidity owing to abortion. PAC Services are services offered by the healthcare professionals to women who have had an abortion to prevent complications related to Abortion. This study aimed to assess the factors influencing PAC service utilization among women of reproductive age in Lira City. Methods This was a quantitative cross-sectional study done among women of reproductive age in Lira City. A total of 335 women were recruited by multistage sampling. The data was collected using a pre-tested structured questionnaire. Ethical approval was obtained. Data was analyzed using SPSS version 23. Results The mean age of study participants was 26.09. (87%) Of the participants were Christians 54.3% (182) had heard about PAC, and the majority, 55.5% (186), had some knowledge about PAC. Most participants (63.9%) stay 1-5km away from the health facility. Stigma was the most common (59.1%) challenge women who had an abortion faced in the community. 26.6% of the participants said health providers of abortion services are kind. Only marital status remained statistically significant at multivariate analysis, P-value (0.009 OR 4.907[0.870-8.266]. Age, religion, and income level are significant in determining whether one will have an abortion or not at p-values of 0.004, 0.009, and 0.029, respectively. Conclusion Education level, marital status, and knowledge increased utilization of PAC services, while factors like stigma and restrictive abortion laws decreased utilization of services. Recommendations The restrictive abortion laws, which allow abortion only if the life of the mother and/or the fetus is in danger, should be adjusted to include adolescents and young women who are not ready for childbearing.